Lithuanian and English request strategies and politeness - Hilbig, Inga (Lietuvių kalba, 2009)
Requests are among the most studied speech acts in the area of interactional pragmatics and linguistic politeness. Empirical studies have proliferated over the past decades; however, although requests in many Western languages, including English, have received significant attention, this paper is the very first attempt to explore request strategies in Lithuanian. The research is based on an assumption about three main universal directness levels in requests as well as on a distinction between positive (closeness, solidarity) and negative (distance, deference) politeness systems. The data has been collected by means of the Discourse Completion Test, which is an open-ended questionnaire with socially divergent situations to prompt requests. It was filled in by 100 Lithuanian university undergraduates and 100 English university undergraduates. The findings demonstrate that while both groups mostly opted for conventionally indirect requests (e.g. indirect questions about the hearer’s ability or willingness to fulfil a request), the Lithuanian responses spread much wider along the directness-indirectness continuum, the respondents employing notably more direct (e.g. imperatives, explicit performatives) as well as a slightly larger number of non-conventionally indirect strategies (hints). Indirect structures do not necessarily convey politeness, just as blunt requests per se are not impolite. No linguistic group of people can be legitimately considered more or less polite than the other, but rather polite in their own socio-culturally acceptable way. Conventionally indirect requests are commonly associated with the negative positive politeness system, whereas direct requests with the positive politeness orientation. The results of the present investigation reveal that Lithuanians are more inclined towards positive politeness, but this is still to be confirmed by further research.